2008
DOI: 10.37358/rc.08.9.1944
|View full text |Cite
|
Sign up to set email alerts
|

Multisensor for Clinical Analysis with Impact on Public Health Evaluation

Abstract: The objective of this paper was to study the suitability of multi gate ion sensitive field effect transistors (ISFETs) for clinical work with specific requirements in the public health evaluation. The obtained sensors were used in a flow cell assembly provided by Bellhouse Medical Products. As in our previous work [1], the sensors were intended for use in the analysis of biological fluids, where the concentrations of specific ions as sodium, potassium and calcium are of critical importance. The electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The statistical analysis of our database comprising 29 patients treated in our hospital revealed that there were 25 women (86.2%) and only 4 men (13.8%), with a female to male ratio of 6.1:1, with a mean age of 54.93 years - Table 1. More than a half (51.72%) were aged between 40 and 60, over one third (37.93%) between 60 and 80 and only 10.34% were aged under 40, similar results being reported in a study performed in Argentina (14). 37.93% 11 As many authors consider, the main symptoms are flank pain and fever.…”
Section: Resultssupporting
confidence: 75%
“…The statistical analysis of our database comprising 29 patients treated in our hospital revealed that there were 25 women (86.2%) and only 4 men (13.8%), with a female to male ratio of 6.1:1, with a mean age of 54.93 years - Table 1. More than a half (51.72%) were aged between 40 and 60, over one third (37.93%) between 60 and 80 and only 10.34% were aged under 40, similar results being reported in a study performed in Argentina (14). 37.93% 11 As many authors consider, the main symptoms are flank pain and fever.…”
Section: Resultssupporting
confidence: 75%
“…Quality of life of patients from our study, with diabetes and lung cancer, was also negatively influenced, especially by the presence of neuropathy, that can be determined by both diabetes and chemotherapy [26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…If, by contrary, the solution would contain only the interfering ion, i, calcium -selective microelectrode's potentiometric answer becomes: (2) where: E Ca,i -electrochemical potential of the calcium selective microelectrode in solution containing only interfering ion, i (mV), a i -chemical activity of interfering ion, i, and stands for selectivity coefficient of calcium against interfering ion, i.…”
Section: Solid-state Calcium Selective Microelectrodementioning
confidence: 99%
“…During last years, important progress has been obtained in the area of biological and clinical analysis using ion selective electrodes with membranes based on macrocyclic transporters [1][2][3]. In potentiometric methodology, a significant development was represented by the ion selective electrodes.…”
mentioning
confidence: 99%